Review on the role of women along the aquaculture value chain in Kenya - Mercy Chepkirui; Paul Sagwe Orina; Tonny Orina; Cecilia Githukia; Jared Ochingo; Judith Kemunto Achoki (Annals of Marine Science - Peertechz Publications, 2023)
Aquaculture is perceived as masculine work in most regions despite several years of women's involvement in the sector. Women participate in almost all activities of the aquaculture value chain such as pond construction, sorting of seeds, fertilization of ponds, making and mending of fishing gears, fish harvesting, processing, value addition, transport, and marketing. The majority of women engage in aquaculture to earn income and food for the household. Women's involvement in aquaculture has led to the creation of more job opportunities thus increasing income generation for rural women. Nevertheless, women face several challenges in aquaculture with the most critical one being limited access to income despite their heavy involvement. They also lack limited access to certified seed, high cost of feeds, and collaterals to access credit. The promotion of aquaculture, gender equity, and empowerment of women and youths has been promoted through various initiatives including Sustainable Development Goals and Blue Economy. However, gender discrepancies are still high despite both gender playing fundamental roles in aquaculture development. Therefore, there is a need to promote gender equity as it will lead to recognition of their full potential towards increasing production, productivity, processing, trade, and economic growth.